1985
DOI: 10.1037/0022-3514.48.3.746
|View full text |Cite
|
Sign up to set email alerts
|

Negative ions and behavior: Impact on mood, memory, and aggression among Type A and Type B persons.

Abstract: Individuals scoring high (Type As), intermediate, or low (Type Bs) on the Jenkins Activity Survey were given an opportunity to aggress against a stranger who, previously, had either provoked or not provoked them. The opportunity to aggress (as well as all other aspects of the study) took place in the presence of (a) a high concentration, (b) a moderate concentration, or (c) a low (ambient) concentration of negative air ions. Results indicated that exposure to moderate or high levels of negative ions significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 27 publications
6
38
0
Order By: Relevance
“…Fifteen studies on activation, anxiety, and mood examined the effects of negative air ions only [5,9,10,12,14,18,26,28-35]. Tom et al [34] utilized a double-blind randomized controlled study to determine the impact of negative air ions on mood in 56 adults (age range: 17–61; mean age: 23).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies on activation, anxiety, and mood examined the effects of negative air ions only [5,9,10,12,14,18,26,28-35]. Tom et al [34] utilized a double-blind randomized controlled study to determine the impact of negative air ions on mood in 56 adults (age range: 17–61; mean age: 23).…”
Section: Resultsmentioning
confidence: 99%
“…Although, conceptually, Type A individuals who are provoked should engage in more aggressive behavior than Type B individuals, the available empirical findings are mixed. Two studies have found that Type A individuals were no more aggressive in their behavior than Type B individuals under provoking conditions (Baron, Russell, & Arms, 1985;Holmes & Will, 1985). Another study showed that Type A individuals behaved more aggressively than Type B individuals under both neutral and provoking conditions (Check & Dyck, 1986).…”
Section: Type a Personalitymentioning
confidence: 99%
“…The effects that have been studied include physiological indices like: temperature, blood pressure, pulse rate ( Yaglou et al, 1933;Herrington, 1935;Herrington and Kuh, 1938;Erban, 1959;Minkh, 1961;Albrechtsen et al, 1978), as well as a variety of cognitive and performance variables including alertness and vigilance (Chiles et al, 1960;McDonald et al, 1967;Albrechtsen et al, 1978;Brown and Kirk, 1987 ); and reaction time (Slote, 1961 ;Halcomb and Kirk, 1965;Hawkins and Barker, 1978;Tom et al, 1981). In addition, quite a few studies focused on possible effects of air ions on mood or emotional variables (Yaglou, 1961;Sigel, 1979;Chany and Hawkinshire, 1981;Hawkins, 1981;Baron et al, 1985;Deleanu and Stamatiu, 1985;Giannini et al, 1986;Hedge and Collis, 1987). During or following these exposures, which have lasted fiom minutes to days, the above variables were evaluated.…”
Section: Mood and Performancementioning
confidence: 99%